Peran Panti Asuhan dalam Membentuk Kepribadian Anak di Panti Asuhan Putra Muhammadiyah Lubuk Basung - Musnaini Musnaini; Hidayani Syam (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The study question is: How does the Lubuk Basung Muhammadiyah Orphanage for boys shape the personalities of the children who live there? What elements encourage and hinder these formative experiences? The aim of this research is to identify the elements that encourage and inhibit the personality development of children at the Putra Muhammadiyah Lubuk Basung Orphanage, as well as the role of the orphanage in this process. This research design is qualitative, but also has descriptive elements because it seeks to fully characterize and clarify the issues raised. The participants in this research were thirty foster children and caregivers at the Putra Muhammadiyah Lubuk Basung Orphanage, three additional caregivers, and one caretaker. Interviews and observations were used as research tools, and qualitative analysis was carried out. Research findings show that personality development is a difficult process, therefore it is very important to develop children's personalities at the Putra Muhammadiyah Lubuk Basung Orphanage. by advising children to exercise discipline by studying the Koran and studying on time, by emphasizing the need to tell the truth and not hide anything, and by implementing strict guidelines to ensure that foster children in orphanages do not make any mistakes.